Archives of Anti-Colonial Resistance and the Liberation Struggle (AACRLS): An integrated programme to fill the colonial gaps in the archival record of Namibia - Namhila, Ellen N. (Journal for Studies in Humanities and Social Sciences, 2015)
National archives inherited from former colonial regimes suffer from a distorted record that marginalised the colonised people, and ignored or misrepresented their efforts for self-determination. The Archives was further depleted by the removal of vitally important records to the colonizing metropolis. As a result, the value of the archives as the memory of the entire nation is diminished. The article describes the efforts by the National Archives of Namibia to rectify this situation through a programme of repatriating or copying migrated, displaced and shared archives, collecting private records and oral history, and popularizing the history of anti-colonial struggles. It concludes that despite considerable successes, the task at hand is far from accomplished and needs further sustained effort.